Reabilitação estética anterior através de prótese fixa metal-free: relato de caso - Queiroz, Thayane Gonçalves [UNESP] (2017)
The rehabilitation of an anti-aesthetic smile in the anterior region is a clinic challenge. The reestablishment of an esthetic and function of anterior teeth can be reached with a correct treatment planning using metal-free dental crowns to provide an esthetic smile. In the presented case report, the patient SAGS, 53 years old, female gender, attended the Partial Fixed Prosthesis Clinic, at Araçatuba Dental College - FOA/UNESP in 2015 complaining about her anterior teeth being ugly and with appearing root. With a clinical examination, it was verified the presence of cemented acrylic resin crowns in the elements 12, 11, 21 and 22, with exposure of the cervical border and the root portion of 12, 11 and 21, besides an unsatisfactory esthetic. In the radiographic examination, it could be noticed the presence of a metal post in tooth 22, and also, the teeth 11 and 21 presented endodontic treatments being satisfactory. Therefore, it was suggested the confection of a metal-free crowns on the four incisor superior teeth with e.max Press system (Ivoclar Vivadent). After esthetic trial and initial occlusal adjustments, the crowns were prepared for the resinous cementation with system Variolink II (Ivoclar Vivadent). The transparent cement was previously selected through trials with the Try-In kit. The crowns were adjusted according to the anterior and canine guide. The final esthetic and functional result was approved by the patient and by professionals involved, in accord to the studies that point the effectiveness of the new resinous adhesive systems associated with the ceramic crowns for the anterior esthetic rehabilitation